Jamaican Dancehall: Demasking the grotesque realism of race and class in ghetto 'gangsta' performance. Issue 2 (4th May 2019) - Goodrich, Lisa Williams
ABSTRACT: This article considers the self-conscious, exaggerated performance of gangster ghetto subjectivities by the younger and more media savvy generation of Jamaican 'gangster dancehall' artists as an example of resistant subjectivization. Through masquerade and hyperbolic visual representations of the 'grotesque' black body, resistant subjectivization facilitates the questioning and transgression of dominant narratives which negatively cast the black body as 'monstrous.' At the same time, the commercialization of gangster dancehall and the grotesque dancehall subject is seen as contributing to the reinforcement of unfavorable stereotypes of the black subject. This potentially undermines the element of resistance in the counterhegemonic discourse of gangster dancehall and leads to tension, not only between hegemonic and counter-hegemonic narratives on black subjectivities, but also between the counterhegemonic discourses within gangster dancehall itself. Through the critical explorations of writings by Jacques Lacan, Stuart Hall, Judith Butler, Julia Kristeva, Franz Fanon and Homi Bhahba, this paper tries to establish whether or not this performance of the monstrous black self indeed represents a form of empowerment for the black ghetto subject in postcolonial Jamaica.